Risk Management in Indian Public Sector Banking: An Empirical Analysis of Credit, Market, and Operational Risks Under Basel III - Savitha Sukumar; Sandhya Balasubramanian (Journal of Risk and Financial Management, 2026)
Indian public sector banks (PSBs) operate under Basel III guidelines, which mandate capital adequacy, liquidity standards, and systematic risk management across credit, market, and operational risk dimensions. This study analyses Basel III Pillar 3 disclosure reports and Reserve Bank of India published data for all twelve PSBs in India for the period 2021–2025, examining capital requirements for credit, market, and operational risks, gross and net non-performing assets, capital adequacy ratios, and return on assets. The study period spans the transition from forbearance-supported stability in 2021 to organic recovery evidenced by declining gross nonperforming asset ratios and improved capitalisation by 2025. Coefficient of variation, Kruskal–Wallis non-parametric tests, one-way ANOVA, and Tukey HSD post hoc analysis reveal significant inter-bank variation across all capital requirement variables, nonperforming asset levels, and CRAR. Further, return on assets does not vary significantly across banks. The study provides empirical confirmation of a systemic capital buffer in Indian banking across both the pandemic stress period and the organic recovery period. Sector mean CRAR rose from 14.40% in 2021 to 17.64% in 2025, while sector mean GNPA declined from 7.5% to 2.2% over the same period, with all twelve banks maintaining CRAR above both the RBI-prescribed minimum. Post hoc analysis attributes credit risk capital variation almost entirely to State Bank of India’s scale, with no significant differences among the remaining eleven banks. These findings have direct implications for national financial stability and systemic risk management in an emerging market context.